2008
DOI: 10.1111/j.1551-2916.2008.02689.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Hydrothermal Synthesis of Pure BiFeO3 Nanopowders Using Triethanolamine and Their Applications as Visible‐Light Photocatalysts

Abstract: BiFeO3 (BFO) nanopowders were synthesized at low temperatures via a hydrothermal process with the aid of triethanolamine (TEA) and their structural, optical, and photocatalytic properties were investigated. As a result of a strong reaction between TEA and Fe ions, pure BFO nanopowders without any secondary phases could be synthesized at temperatures as low as 130°C. BFO nanopowders exhibited a strong absorption in the visible‐light regime, which resulted in the efficient photocatalytic activity for decompositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(60 citation statements)
references
References 23 publications
5
54
0
1
Order By: Relevance
“…Blank tests (pure RhB aqueous solution without BFO) under visible light showed that only 3 % of RhB decomposed after 4 h irradiation, which indicated that the RhB is resistant to decomposition under visible-light irradiation. However, in the presence of the BiFeO 3 as photocatalyst, more than 40 % of RhB was decomposed after 4 h visible-light irradiation, which is comparable with that of another report [35]. The above result proves that the photocatalytic activity of BFO powders is quite efficient and indicates that BFO powders are promising visible-light photocatalysts.…”
Section: Methodssupporting
confidence: 91%
“…Blank tests (pure RhB aqueous solution without BFO) under visible light showed that only 3 % of RhB decomposed after 4 h irradiation, which indicated that the RhB is resistant to decomposition under visible-light irradiation. However, in the presence of the BiFeO 3 as photocatalyst, more than 40 % of RhB was decomposed after 4 h visible-light irradiation, which is comparable with that of another report [35]. The above result proves that the photocatalytic activity of BFO powders is quite efficient and indicates that BFO powders are promising visible-light photocatalysts.…”
Section: Methodssupporting
confidence: 91%
“…Nanosized BiFeO 3 powders have been reported to exhibit weak ferromagnetism at room temperature, which is different from the magnetic property of bulk samples [7,8]. Furthermore, BiFeO 3 nanopowders have shown the prominent visible-light photocatalytic activity that is ascribed to the small bandgap and the high surface area of nanosized BiFeO 3 [8,9]. These nanosize-induced properties are expected to widen the potential applications of BiFeO 3 .…”
Section: Introductionmentioning
confidence: 94%
“…To obtain nano-crystalline powders with high homogeneity and uniform structure, many techniques have been provided for the synthesis of the BiFeO 3 powders. These methods are coprecipitation [8], hydrothermal [9][10][11][12][13][14], solvothermal [15,16], sonochemical [17], microemulsion [17], polyacrylamide gel [18], ferrioxalate [19], sol-gel [6,[20][21][22][23], combustion synthesis [7,[24][25][26], molten-salt [27][28][29], tartaric acid-assisted gel strategy [30], polymeric precursor [31,32] and mechanochemical synthesis [33]. The chemical co-precipitation method ensures proper distribution of the various metals ions resulting to stoichiometric and smaller particles size product, compared to some of the other procedures.…”
Section: Introductionmentioning
confidence: 99%